Project Genome: Wireless Sensor Network for Data Center Cooling - Liu, Jie; Zhao, Feng; O'Reilly, Jeff; Souarez, Amaya; Manos, Michael; Liang, Chieh-Jan Mike; Tersiz, Andreas (The Architecture Journal, 2008)
The IT industry is the one of the fastest growing sectors of the U.S. economy in terms of its energy consumption. According to a 2007 EPA report, U.S. data centers alone consumed 61 billion kWh in 2006 — enough energy to power 5.8 million average households. Even under conservative estimates, IT energy consumption is projected to double by 2011. Reducing data center energy consumption is a pressing issue for the entire IT industry now and into the future. In this article, we argue that dense and real-time environmental monitoring systems are needed to improve the energy efficiency of IT facilities.